CYP19A1 TC/CC Polymorphism, along with Deletion of GSTM1 and GSTT1 Genes, Strongly Influences Female Infertility Risk - Maria Manuel Casteleiro Alves; Micaela Almeida; António Hélio Oliani; Luiza Breitenfeld; Ana Cristina Ramalhinho (MDPI AG, 2023)
Oxidative stress has a fundamental role in the pathophysiology of various conditions, like infertility. This case-control study was performed to assess the potential role of CYP19A1, GSTM1, and GSTT1 in modifying individual predisposition to female infertility. Genotyping of 201 women with established infertility and 161 fertile female controls was performed, and statistical associations were analyzed. For carriers of GSTM1 null genotype along with CYP19A1 C allele, there is a significant association with female infertility risk (OR 7.023; 95% CI (3.627-13.601; p < 0.001), and, also for carriers of GSTT1 null genotype along with the CYP19A1 TC/CC genotype (OR 24.150; 95% CI (11.148-52.317; p < 0.001). A positive association with female infertility risk for carriers of the C allele in CYP19A1 and null genotypes in GTSM1 (OR 11.979; 95% CI (4.570-31.400; p < 0.001) or GSTT1 (OR 13.169; 95% CI (4.518-38.380; p < 0.001) was found. When both GSTs are deleted, the risk of developing female infertility is significant, independently of the CYP19A1 genotype; when all the presumed high-risk genotypes are present, we found a significant association with female infertility risk (OR 47,914; 95% CI (14,051-163,393; p < 0.001).